PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PENGGUNA JASA TRAVEL CV. PANCA INDRA ABADI WISATA SIDOARJO - AYU AGUSTIANINGSIH, EKA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Competition in services is very competitive, especially service travel. Finally, a variety of service businesses competing to attract consumers of travel services, respectively. This study aims to identify and analyze the effect of service quality towards customer satisfaction the user of travel CV. Panca Indra Abadi Wisata Sidoarjo. The population in this study is students economic education who use the services travel CV. PIA Wisata Sidoarjo, the size of the sample used in this study was 192 respondents. Data analysis tools used in this study is a simple regression analysis and data collection questionnaire as respondents. Based on the R Square resulting value of 0.403, means that service quality influenced customer satisfaction PIA Wisata Sidoarjo by 40.3%, while the remaining 59.7% are caused by the other factors. The results showed that there was a significant effect of the variable quality of services to customer satisfaction of service users travel CV. Panca Indra Abadi Wisata Sidoarjo. Keywords : Quality of service, Customer Satisfaction